Electromagnetic oscillations at the edge of the Uragan-3M plasma - Pashnev, V.K.; Tarasov, I.K.; Tarasov, M.I.; Sitnikov, D.A.; Tsybenko, S.A.; Pinos, I.B.; Stepanov, K.N.; Olshansky, V.V.; Shvets, O.M.; Sorokovoy, E.L.; Petrushenya, A.A.; Lozin, A.V.; et al. (Вопросы атомной науки и техники, 2013)
In the Uragan-3M torsatron the plasma is ICRF heated with the use of antennas of different types. The objective of this work is to study the electromagnetic wave propagation outside the plasma confinement volume and the effect of these waves on confined plasma behavior during RF-heating. В торсатроне Ураган-3М плазма нагревается ВЧ-волнами вблизи ионно-циклотронного резонанса антеннами различных типов. Целью настоящей работы является изучение распространения электромагнитных волн вне объема удержания и влияния этих волн на параметры плазмы в течение разряда. У торсатроні Ураган-3М плазма нагрівається ВЧ-хвилями поблизу іонного-циклотронного резонансу антенами різних типів. Метою цієї роботи є вивчення поширення електромагнітних хвиль поза обсягу утримання і впливу цих хвиль на параметри плазми протягом розряду.